(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Organic drug synthesis is a fundamental process in pharmaceutical research and development, involving the design and preparation of bioactive molecules for therapeutic use. Conventional synthetic methods often require extensive experimentation, making the process time-consuming, costly, and resource-intensive. Artificial Intelligence (AI) has emerged as a transformative technology that enhances the efficiency and accuracy of organic drug synthesis by integrating advanced computational techniques into the drug discovery workflow. AI techniques, including machine learning, deep learning, and neural networks, analyse large volumes of chemical and biological data to predict reaction outcomes, identify optimal synthetic pathways, optimise reaction conditions, and estimate reaction yields. In retrosynthetic analysis, molecular design, and reaction planning, AI-powered platforms like IBM RXN, ASKCOS, DeepChem, and AiZynthFinder help researchers avoid repeating laboratory experiments. These tools not only accelerate the discovery of novel drug candidates but 6also contribute to sustainable pharmaceutical manufacturing by minimising chemical waste, reducing development costs, and improving overall process efficiency. The reliance on high-quality datasets, computational complexity, limited model interpretability, and ongoing requirement for expert validation all present challenges for AI-based drug synthesis, despite its significant advantages. However, it is anticipated that ongoing advancements in computational chemistry and AI algorithms will overcome these limitations and strengthen its applications in medicinal chemistry. In conclusion, approaches to pharmaceutical research that are data-driven and faster are being made possible by artificial intelligence, which is revolutionizing organic drug synthesis. The integration of AI into synthetic chemistry has the potential to significantly accelerate drug discovery, improve productivity, and support the development of safer, more effective, and environmentally sustainable therapeutic agents.